Inverse Electron-Demand Diels–Alder Reaction of Pyrazines with 2,5-Norbornadiene as Acetylene Precursor - Krinochkin, Alexey P.; Valieva, Maria I.; Kudryashova, Ekaterina A.; Potapova, Svetlana S.; Potapova, Anastasia P.; Fatykhov, Ramil F.; Khalymbadzha, Igor A.; Sharapov, Ainur D.; Kopchuk, Dmitry S.; Kovalev, Igor S.; Petrova, Victoria E.; Krivoshchapov, Nikolai V.; Zyryanov, Grigory V. (Synthesis, 2025)
The reaction of pyrazines with 2,5-norbornadiene, an acetylene precursor, as a cascade of Diels–Alder reactions is reported yielding substituted pyridines. In contrast to the known examples of intermolecular Diels–Alder type reaction of pyrazines with acetylene, which usually leads to a mixture of products, in our case the formation of a single isomer was observed. The proposed approach allows the conversion of pyrazines with different types of substitution, except those containing methyl and amino donor groups, to pyridines. In addition, highly functionalized aminonicotic esters were obtained, which can be used for the synthesis of bioactive compounds. An unusual course of the Diels–Alder reaction was found in the case of tetrasubstituted pyrazines, which cleave organic nitriles instead of HCN. Quantum-chemical modeling of possible transition states showed that this Diels–Alder reaction proceeds via cycloaddition of 2,5-norbornadiene to pyrazine with sequential elimination of HCN and cyclopentadiene; the reaction pathway including initial formation of acetylene from norbornadiene and subsequent Diels–Alder reaction with the acetylene was rejected as kinetically unfavorable.
Keywords: pyrazine; pyridine; inverse-electron-demand Diels–Alder reaction; 2,5-norbornadiene